A qualitative examination of patients experiences of dietitians ' consultation engagement styles within nephrology. Issue 1 (23rd August 2017) - Morris, A.; Herrmann, T.; Liles, C.; Roskell, C.
Abstract: Background: Dietitians provide individuals with tailored, practical nutritional advice. For this reason, skills in effective interpersonal communication are essential. In the case of chronic kidney disease, the specifics of dietary advice may change according to renal function. The conveyance of accurate dietary advice and compliance is critical and requires full engagement with the service. The effect of communication styles on patients ' engagement experiences with renal dietetics is unknown. Accordingly, the present study aimed to explore patients ' engagement experiences with renal dietitians. Methods: A qualitative phenomenology study using semi‐structured in‐depth interviews was undertaken with 20 adult renal service users who had engaged with renal dietitians to receive dietary advice. Interpretive phenomenological analysis was used to analyse data. Results: Two main themes emerged from consultation experiences: helpful and unhelpful engagement styles. Individuals reporting helpful engagement styles experienced dietitians ' communication as empathetic, demonstrating positive regard for their lifestyles. However, individuals who reported experiences of unhelpful engagement styles found dietetic care indifferent and communication styles paternalistic. These individuals continued to engage reluctantly despite unhelpful engagement experiences, but felt disempowered. These diverse experiences of engagement can be interpreted by means of 'ego states' within the theoretical model of transactional analysis (TA). Adult ego states may underpin a helpful engagement style whilst a dietitians ' parental ego state was more likely to precipitate an unhelpful engagement style. Conclusions: Ego states, in the context of TA theory, can help to explain the way in which patients engage with renal dietitians. Attention should be given to the employment of a humanistic approach within dietetic consultations. Dietitans need to ensure that they can demonstrate expertise and confidence in the specific communication skills required for patient‐centred care.